Pengaruh Peer Assessment dalam Meningkatkan Keterampilan Anamnesis di Skills Laboratory - Indah Puspasari Kiay Demak; Amitya Kumara; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Peer assessment is a breakthrough innovation in assessment method where students assess their fellows. The benefits of it are feedback, cognitive and metacognitive gain, motivation, collaborative learning, self-regulated learning and performance enhancement. Learning in skills laboratory, students are expected to be able to master not only knowledge but also skills. Peer assessment is expected to make students be more motivate in learning and enhance performance. The aim of this study is to find out whether peer assessment can enhance students’ medical interview skills in skills laboratory.Method: The method was a quasi-experiment study with matching-only pretest posttest control group design. The subjects were third-year students in Medical School of Tadulako University which were divided into 2 experiment groups and 2 control groups. Before giving treatment, the skills of students in all group were assessed (pre test). After the treatment, post test was held as an evaluation tool. The raising score from pre test to post test will be analyzed with student t test.Results: P value for raising score was 0,907 (á > 0.05) with mean difference -0.091, which means statistically not significant. The negative number of mean difference indicate that the raising score in experiment group was lower than in control group.Conclusion: Raising score in control group was higher than in experiment group, but not significance statistically. Application of peer assessment in skills laboratory should be more concern in students ability in assessing which can be obtain by intense training and continuous monitoring and feedback from instructor.